The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/tox.20726
|View full text |Cite
|
Sign up to set email alerts
|

Influence of increasing temperature and salinity on herbicide toxicity in estuarine phytoplankton

Abstract: Ecological risk assessments are, in part, based on results of toxicity tests conducted under standard exposure conditions. Global climate change will have a wide range of effects on estuarine habitats, including potentially increasing water temperature and salinity, which may alter the risk assessment of estuarine pollutants. We examined the effects of increasing temperature and salinity on the toxicity of common herbicides (irgarol, diuron, atrazine, and ametryn) to the phytoplankton species Dunaliella tertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Of particular consideration is also the impact of climate change on contaminant toxicity. For instance, under climate change effects on temperature, salinity, and pH , empirical studies on toxicity testing of pesticides in phytoplankton and invertebrates have shown increased toxicity by 4–5 times at higher temperatures and salinities relative to standard conditions (see DeLorenzo, Danese & Baird, ; DeLorenzo, Wallace, Danese & Baird, ). Conversely, pollutant‐induced climate change susceptibility conspires against the adaptability of organisms and food webs to make levels of biological organization more vulnerable to climate change risk and impacts, thus reducing ecosystem resiliency.…”
Section: Climate Change–pollutant Bioaccumulation Interactions: Towarmentioning
confidence: 99%
“…Of particular consideration is also the impact of climate change on contaminant toxicity. For instance, under climate change effects on temperature, salinity, and pH , empirical studies on toxicity testing of pesticides in phytoplankton and invertebrates have shown increased toxicity by 4–5 times at higher temperatures and salinities relative to standard conditions (see DeLorenzo, Danese & Baird, ; DeLorenzo, Wallace, Danese & Baird, ). Conversely, pollutant‐induced climate change susceptibility conspires against the adaptability of organisms and food webs to make levels of biological organization more vulnerable to climate change risk and impacts, thus reducing ecosystem resiliency.…”
Section: Climate Change–pollutant Bioaccumulation Interactions: Towarmentioning
confidence: 99%
“…The other modification revealed from proteome analysis was an up-regulation of bacterioferritin co-migratory protein-homologue peroxiredoxin-Q (PRX-Q) (Das and Bagchi 2011). Salinity and temperature are reported to enhance herbicide toxicity (DeLorenzo et al 2011). Consequently, herbicide resistance in a DCMU-resistant mutant of Prophyridium sp.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that a HW exposure (5 days, C: 25°C, H: 35°C) generally decreased the negative effects of the herbicides on the chlorophyll-a concentration, lipid content and starch content (Figure 5). However, opposite to Tasmin et al (2014), under simultaneous exposure to HW and herbicides, growth rate and cell density were generally decreased compared with the treatment containing only herbicides (Figure 5; Delorenzo et al, 2013).…”
Section: Combined Effects Of Hws and Micropollutants On Primary Produ...mentioning
confidence: 93%